Aplikasi Teori Fungsi Interpretasi Jorge J.E. Gracia tentang HadÃ®th Kebiri - Zamawi, Bahruddin (Koordinatorat Perguruan Tinggi Agama Islam Swasta Wilayah IV Surabaya, 2016)
The paper highlights the contradiction of two hadÃ®ths on castration. The context of the issue has appeared within the contemporary Indonesia right after the Government stated the âadditional punishmentâ for those who commit sexual harassment. The spirit of the punishment is to give a sort of âdaunting effectâ for the committers and âpossible predatorsâ. Such additional punishment has, however, invited various different responses from the Indonesian people. Some have rejected it, while some other have intensely called for its implementation. Regardless of this debate, article will shed light on the historical narration of Islamic view on castration in Muhammadâs life. The research finds that there are two hadÃ®ths which are regarded as contradictory. The first hadÃ®th has narrated that Muhammad banned his companions to geld themselves. This happened when Muhammad and his companions went to battle field. Another hadÃ®th has, however, reported that Muhammad allowed one of his companions to geld himself. These two seemingly conflicting hadÃ®ths need further care-ful explanations in order to reach the best and proper under-standing. In doing so, the author employs Graciaâs theory on the Function of Interpretation.